Revisiting the mechanics and energetics of walking in individuals with chronic hemiparesis following stroke: from individual limbs to lower limb joints - Farris, Dominic James (J Neuroeng Rehabil, 2015)
BACKGROUND: Previous reports of the mechanics and energetics of post-stroke hemiparetic walking have either not combined estimates of mechanical and metabolic energy or computed external mechanical work based on the limited combined limbs method. Here we present a comparison of the mechanics and energetics of hemiparetic and unimpaired walking at a matched speed. METHODS: Mechanical work done on the body centre of mass (COM) was computed by the individual limbs method and work done at individual leg joints was computed with an inverse dynamics analysis. Both estimates were converted to average powers and related to simultaneous estimates of net metabolic power, determined via indirect calorimetry. Efficiency of positive work was calculated as the ratio of average positive mechanical power [Formula: see text] to net metabolic power. RESULTS: Total [Formula: see text] was 20% greater for the hemiparetic group (H) than for the unimpaired control group (C) (0.49 vs. 0.41 W · kg(−1)). The greater [Formula: see text] was partly attributed to the paretic limb of hemiparetic walkers not providing appropriately timed push-off [Formula: see text] in the step-to-step transition. This led to compensatory non-paretic limb hip and knee [Formula: see text] which resulted in greater total mechanical work. Efficiency of positive work was not different between H and C. CONCLUSIONS: Increased work, not decreased efficiency, explains the greater metabolic cost of hemiparetic walking post-stroke. Our results highlighted the need to target improving paretic ankle push-off via therapy or assistive technology in order to reduce the metabolic cost of hemiparetic walking.